Clinical Studies in the Intensive Care Unit - Ethical and Legal Aspects - Deutsch, Erwin (Victoria University of Wellington Law Review, 1997)
This article draws on international experience to explore the ethical and legal aspects of performing clinical studies on patients in intensive care units. It discusses aspects of consent relevant to clinical studies in this medical environment, it considers the involvement of ethical committees, and the role and appropriate level of insurance cover.